Structure of thermally evaporated bismuth selenide thin films - Rogacheva, E.I.; Fedorov, A.G.; Krivonogov, S.I.; Mateychenko, P.V.; Dobrotvorskay, M.V.; Garbuz, A.S.; Nashchekina, O.N.; Sipatov, A.Yu. (Functional Materials, 2018)
The Bi₂Se₃ thin films with thicknesses d = 7-420 nm were grown by thermal evaporation in vacuum of stoichiometric n-Bi₂Se₃ crystals onto heated glass substrates under optimal technological conditions determined by the authors. The growth mechanism, microstructure, and crystal structure of the prepared thin films were studied using X-ray diffraction, scanning electron microscopy, energy-dispersive X-ray spectroscopy, X-ray photoelectron spectroscopy, and atomic force microscopy. It was established that the prepared thin films were polycrystalline, with composition close to the stoichiometric one, did not contain any phases apart from Bi₂Se₃, were of a high structural quality, and the preferential growth direction [001] corresponded to the direction of a trigonal axis C₃ in a hexagonal lattice. The films, like the initial crystal, exhibited n-type conductivity. It was shown that with increasing film thickness, the grain size and the film roughness remain practically the same at thicknesses d << 100 nm, and after that increase, reaching their saturation values at d ~ 300 nm. It follows from the results obtained in this work that using the method of thermal evaporation in vacuum from a single source, one can prepare thin n-Bi₂Se₃ films of a sufficiently high structural quality with a composition close to the stoichiometric one and the preferential growth orientation.